2016
DOI: 10.1210/jc.2016-1806
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Insulin Signaling in Acromegaly: Impact of Surgery Versus Somatostatin Analog Treatment

Abstract: Background: Erythropoietin (Epo) exerts direct effects on white adipose tissue (WAT) in mice in addition to its erythropoietic effects, and in humans Epo increases resting energy expenditure and affect serum lipid levels, but direct effects of Epo in human WAT have not been documented. We therefore investigated the effects of acute and prolonged Epo exposure on human WAT in vivo. Method: Data were obtained from two clinical trials: 1) acute Epo exposure (rHuEpo, 400 IU/kg) followed by WAT biopsies after 1 h an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
4
7
0
Order By: Relevance
“…Changes in the metabolic status occurred despite the biochemical control of acromegaly due to the SSA therapy. These data are in keeping with previous studies which reported that hyperglycaemia is a common side effect of SSAs.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in the metabolic status occurred despite the biochemical control of acromegaly due to the SSA therapy. These data are in keeping with previous studies which reported that hyperglycaemia is a common side effect of SSAs.…”
Section: Discussionsupporting
confidence: 93%
“…It remains to be tested if a more prolonged study period will translate into detectable changes in QoL or other non-biochemical endpoints. Our observations on insulin, FFA and glucose levels during the OGTT are in accordance with previous studies (11,12,13) and reflect the suppressive effects of SA on insulin secretion. It is also noteworthy that a positive correlation between insulin AUC during OGTT and IGF-I was recorded only in surgery patients, which indirectly supports a suppressive effect of SA on insulin-induced hepatic IGF-I.…”
Section: Discussionsupporting
confidence: 93%
“…IGF-I standard deviation scores (SDS) at the time of acromegaly diagnosis were calculated post hoc based on IGF-I data from each patient record using the corresponding age-related cut-off levels. Serum levels of insulin, glucose and FFA were measured as previously published (13).…”
Section: Hormones and Metabolitesmentioning
confidence: 99%
“…The various therapeutic means of acromegaly have a varied effect on carbohydrate metabolism: in most cases, the surgical treatment allows the concomitant cure of diabetes, the somatostatin analogues and pasireotide have a hyperglycemic effect, and the antagonists of the GH have a hypoglycemic effect [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%